Double-layer control of an automatic mechanical transmission clutch during commercial vehicle start-up - Song, Min (Strojniški vestnik, 2019)
Engagement control of an automatic mechanical transmission clutch during vehicle start-up has important influences on the safety, comfort, service life, energy consumption, and emissions of the vehicle. However, all existing control strategies use single-layer control, which leads to poor temperature adaptability. This paper develops a double-layer control strategy based on an automatic actuator to improve vehicle start-up performance. The governing characteristics of a diesel engine with a variable-speed governor are studied. The working principles and a model of the automatic actuator are described. A simulation of vehicle start-up is constructed and tested. Finally, the double-layer control strategy is verified in an experimental vehicle. The experimental and simulation results show that the double-layer control strategy provides shorter start times, less jerking, and lower friction, thereby demonstrating its effectiveness and practicability.
Keywords: automatic mechanical transmission; clutch engagement controls; double-layer controls; dvonivojsko vodenje; mehanski samodejni menjalniki; postopek speljevanja; regulacija vklapljanja sklopke; start-up processes